PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP JUMLAH PENYAKIT KERJA DAN JUMLAH KECELAKAAN KERJA KARYAWAN PADA PT. HANEI INDONESIA - Putera, Reza Inderadi; Harini, Sri (Fakultas Ekonomi Universitas Djuanda, 2017)
The purpose of this study aims to influence health and safety (K3) to the number of occupational diseases and accidents the number of employees at PT. Hanei Indonesia. The data used for the study is a document of the company. Analysis of the data is processed using simple regression methods to determine the effect of health and safety on the number of occupational diseases and the number of work accidents, the correlation coefficient to determine the relationship, the coefficient of determination to find out the percentage and hypothesis analysis (t-test) to determine the significance of the cost of K3 to the number of disease employment and the number of work accidents. The results showed that the cost of K3 affect the number of ccupational diseases as well as the cost of K3 on the number of workplace accidents.Keywords: Cost K3, Work Diseases and Accidents